Smartphone Resource Management Optimization to Improve Genshin Impact Gaming Performance in Different Configurations - setiawati, disti; Dewina Fitri, Resty; Salsabila Hermawan, Athiyya; Fratiwi, Aprilliana (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
This study aims to analyze the effectiveness of smartphone resource management in improving gaming performance for Genshin Impact across different device configurations. Due to its graphical complexity, Genshin Impact often causes performance issues such as lag, throttling, and overheating—especially on mid- to low-end smartphones. Using a descriptive quantitative approach, data was collected through direct testing with monitoring tools such as PerfDog and GameBench, and supported by questionnaires distributed to 71 respondents. The results reveal that internal resource management—including RAM allocation, CPU/GPU usage, and built-in optimization features—has a significant effect on frame rate stability and thermal performance. Additionally, device specifications, in-game settings, and background app management play crucial roles in maintaining a responsive gaming experience. All research instruments were validated and found reliable. This study provides technical recommendations and ideal device configurations to help users, particularly mid-range smartphone owners, achieve smoother and more efficient Genshin Impact gameplay.